Primary Health Care: Comparing Public Health Nursing Models in Ireland and Norway. (31st March 2013) - Clancy, Anne; Leahy-Warren, Patricia; Day, Mary Rose; Mulcahy, Helen
Abstract : Health of populations is determined by a multitude of contextual factors. Primary Health Care Reform endeavors to meet the broad health needs of populations and remains on international health agendas. Public health nurses are key professionals in the delivery of primary health care, and it is important for them to learn from global experiences. International collaboration is often facilitated by academic exchanges. As a result of one such exchange, an international PHN collaboration took place. The aim of this paper is to analyse the similarities and differences in public health nursing in Ireland and Norway within the context of primary care.